2020
DOI: 10.1007/s00520-020-05548-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to mitigate radiotherapy-induced oral mucositis in head and neck cancer patients

Abstract: Background Oral mucositis is a debilitating consequence of radiotherapy in patients with head and neck cancers. Radiationinduced oral mucositis (RIOM) can cause pain and weight loss, reduce quality of life and affect treatment outcomes. Methods A systematic review was undertaken to identify and examine the efficacy of low-cost interventions to mitigate RIOM and to develop clinical guidelines based on the evidence. Results The author identified three interventions: benzydamine hydrochloride mouth rinse (BHM), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
1
22
0
7
Order By: Relevance
“…However, severe oral mucositis induced by radiotherapy can directly lead to reduced food intake, malnutrition and weight loss. Many studies have investigated in an attempt to reduce mucositis and weight loss [ 19 , 20 ]. Catrina et al [ 19 ] identified twenty-four studies, honey and the use of benzydamine hydrochloride mouthwash were not advised due to the generally poor quality of the research and the scant evidence supporting the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, severe oral mucositis induced by radiotherapy can directly lead to reduced food intake, malnutrition and weight loss. Many studies have investigated in an attempt to reduce mucositis and weight loss [ 19 , 20 ]. Catrina et al [ 19 ] identified twenty-four studies, honey and the use of benzydamine hydrochloride mouthwash were not advised due to the generally poor quality of the research and the scant evidence supporting the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated in an attempt to reduce mucositis and weight loss [ 19 , 20 ]. Catrina et al [ 19 ] identified twenty-four studies, honey and the use of benzydamine hydrochloride mouthwash were not advised due to the generally poor quality of the research and the scant evidence supporting the intervention. Although the authors suggested glutamine as a method to lessen oral mucositis, there is still a need for high-quality studies with a widely accepted technique to help reduce heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 78% of patients in this study received high-dose radiation treatment (70Gy) with systemic therapy. A systematic review of low-cost interventions to treat radiation induced mucositis in head and neck cancer patients identi ed benzydamine hydrochloride mouth rinse, honey and oral glutamine as potential therapeutics [34]. Whilst only glutamine was recommended to mitigate radiation induced mucositis, the lack of its standardised formulation and dose have precluded its robust assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it induces oral mucositis that may favor the emergence of opportunistic infections, fever, anorexia, hemorrhage, severe pain, dysphagia and dysgeusia [111]. Oral glutamine has been recommended to mitigate radiotherapy-induced oral mucositis in head and neck cancer patients but other effective interventions are needed [112]. As mentioned previously, probiotics may participate indirectly in re-epithelization and tissue regeneration due to their potential to: (1) influence immune-regulating factors (e.g., kB nuclear factor, toll-like receptors in dendritic cells), (2) modulate inflammatory mediator levels (e.g., cytokines such as IL-1β, TNF-α, IL-6 and IL-15 and chemokines such as IL-8); and (3) induce the production of proteolytic enzymes involved in tissue remodeling (MMPs).…”
Section: Probiotics In Oral Wound Healing and Oral Mucositis Related With Cancer Therapymentioning
confidence: 99%